From crisis to excellence : change management at Fre`re Hospital in the Eastern Cape (Case A) - Arnold, Bashierah; Bick, Geoff; de Villiers, Katusha (London : Graduate School of Business, University of Cape Town, 2018)
Fre`re Hospital case A presents students with a decision dilemma within a highly challenging and dynamic South African context. The challenges faced by the protagonist, Dr Wagner, provide students with the opportunity to examine possible reactions and change management strategies when placed in a crisis management situation. There are multiple themes presented in the case that contribute to the dilemma facing Dr Wagner. Students must identify the key issues that caused the situation of crisis at the hospital, familiarise themselves with the key problems experienced by the hospital's management, staff and patients, and discuss what management approaches would be appropriate to address these problems. The case questions ask students to place themselves in Dr Wagner's shoes and decide whether or not each would choose to embrace the challenge of continuing as the hospital's CEO.
Originally Published InArnold, B., Bick, G., & de Villiers, K. (2018). From crisis to excellence: Change management at Fre`re Hospital in the Eastern Cape (case A). 2018-8. Cape Town, South Africa: Graduate School of Business, University of Cape Town.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fre`re Hospital (South Africa); Crisis management -- Case studies; Strategic planning -- Case studies